PENGARUH MOTIVASI, KEDISIPLINAN KERJA DAN KOMUNIKASI TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DALAM WILAYAH KOTA JUANG KABUPATEN BIREUEN - Rukayah (JURNAL KEBANGSAAN, 2022)
This study aims to dig further and provide empirical information to find out a). the effect of teacher work motivation on teacher performance, b). the influence of teacher work discipline on teacher performance, c). the effect of teacher work communication on teacher performance and d). the simultaneous influence of teacher work motivation, teacher work discipline and teacher work communication on the performance of elementary school teachers in Juang City, Bireuen Regency. The research was conducted in the District of Kota Juang, Bireuen Regency with the object of research being elementary school teachers. The research instrument used a measurable questionnaire based on the content validity test and the instrument reliability test. The analytical method used is quantitative verification with a path analysis model approach. The results obtained that; 1) there is an effect of teacher work motivation on performance, amounting to 50.17%. 2). There is an influence of work discipline aspects on teacher performance by 38.68%. 3). There is an influence of communication factors on teacher performance, which is equal to 55.95%, and 4). Simultaneously the factors of work motivation, work discipline and communication have a significant effect on teacher performance, with a contribution of 78.1%. While the rest (residual value) the role of variables that are not examined is 21.1%.